Modern Developments in Diabetes Treatment - Yadavar Nikravesh (Iran University of Medical Sciences, 1988)
Extract   Modern societies in comparison to the past have more expectations from nurses. Nowadays beside the nursing care, nurses have other roles such as use of capabilities in providing knowledge to nursing students. Understanding the kind of treatment, nurses would be succeeded in their nursing care. Professional nurses are responsible to accommodate their knowledge with the developing nursing scinse and be able to educate nursing students and connect nursing theories with nursing practice. For example nurses should understand medical knowledge developments and modern techniques in caring of diabetic patients.